Hamka and Quraish Shihab’s View on Zakah Manager - Rahmad Hakim (TSAQAFAH, 2021)
This study aims to analyze the view of Hajj Abdul Malik Karim Amrullah (Hamka) and Quraish Shihab on Zakah Manager study on QS. al-Taubah [9]: 60. This paper is qualitative using the documentation method in data collection. The research used qualitative based on document analysis of all instruments related to works of Hamka and Quraish Shihab on Zakah Manager. At the end of the research, the authors conclude that there are differences and similarities between Hamka's and Shihab's views on the zakah manager. They both have the same opinion regarding the meaning of zakah manager in the QS. al-Taubah [9]: 60. However, they have different opinions on the appointment of zakah manager, where Shihab proposes zakah manager to be appointed by the state in contrast, Hamka stated that zakah manager does not have to be appointed by the state, adjusting to the situation and conditions of the country. Likewise, they have different opinions in the event of misconduct of the zakah manager or if zakat funds are lost. They also differ in the right of the zakah manager in zakat funds. The results of this study contribute to enriching the discourse of zakah management, especially on the legal thought of Zakah Manager.